Factors affecting the reliability of assessing the concrete strength by rebound hammer and cores. (1st June 2017) - Alwash, Maitham; Breysse, Denys; Sbartaï, Zoubir Mehdi; Szilágyi, Katalin; Borosnyói, Adorján
Highlights: Selecting core locations based on rebound measurements improves the assessment reliability. Reducing repeatability of rebound measurements improves the assessment reliability. Increasing the number of cores improves the assessment reliability. Concrete intrinsic variability plays an important role on the assessment reliability. Abstract: To assess concrete strength in a structure, nondestructive technique (NDT) like rebound hammer is combined with destructive technique (coring tests) in order to implement a relationship ''conversion model" between the compressive strength and, NDT measurements. The conversion model is used to estimate the local strength value at each test location using the corresponding NDT value. Then the estimated mean strength and/or estimated strength standard deviation (concrete strength variability) values are calculated. However, the reliability of these estimated values is always a questionable issue because of the uncertainties associated with the strength predictions based upon NDT measurements. To improve the reliability, the uncertainties must be reduced by specifying and controlling their influencing factors. The objective of this paper is to study the reliability of assessment by analyzing the effects of several influencing factors: number of test locations used to identify a conversion model between strength and rebound measurement NC (number of cores), true value of concrete strength variability, within-test variability of rebound measurements, accepted uncertainty level, quantity to be assessed (mean strength, strength variability), model identification approach (like regression) and the way of selection core locations (random or conditional i.e. selection based on NDT measurements from preliminary investigation). To this end, a large campaign of laboratory studies datasets (1700 test results) was considered for the analysis in the present study. Results show that NC, within-test variability of rebound measurements and true concrete strength variability have significant effects on the assessment reliability. Conditional selection of cores has also an important effect on improving the reliability so it is strongly recommended.